2020
DOI: 10.1111/jfpp.14651
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic properties of Eucalyptus caesia and Dracocephalum multicaule Montbr & Auch essential oils: Antimicrobial activity against food borne pathogens and antioxidant activity in pear slices

Abstract: The objective of this study was to evaluate the possible synergistic interactions on antibacterial and antioxidant efficacy of two plant essential oils (EOs) Eucalyptus caesia Benth and Dracocephalum multicaule Montbr & Auch in vitro and in pear slices. Antibacterial combination effect was evaluated against seven important pathogenic bacteria (Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Shigella flexneri, Pseudomonas aeruginosa, Salmonella typhi, and Escherichia coli) using microbroth dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The use of a complex extract may be more advantageous due to the synergistic interaction of the individual components of the extract, which increase the resulting efficiency of such complex mixtures. Hashemi and Jafarpour [61] tested the effectiveness of Eucalyptus caesia Benth and Dracocephalum multicaule complex essential oils on E. coli. They found that essential oils were more effective against Gram-positive than against Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a complex extract may be more advantageous due to the synergistic interaction of the individual components of the extract, which increase the resulting efficiency of such complex mixtures. Hashemi and Jafarpour [61] tested the effectiveness of Eucalyptus caesia Benth and Dracocephalum multicaule complex essential oils on E. coli. They found that essential oils were more effective against Gram-positive than against Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The main components of CEO were thymol, γ‐ terpinene, and p‐cymene and for SEO were carvacrol and myrcene. It has been shown that chemical compounds such as aldehydes, phenolics, carvacrol, thymol, and eugenol play an important role in the antimicrobial properties of EOs (Clemente et al., 2016; Hashemi & Jafarpour, 2020a). It seems that the inactivation of the studied pathogens is related to the impact of volatile compounds of CEO and SEO in the vapor phase.…”
Section: Resultsmentioning
confidence: 99%
“…The interior of the container consists of three sections: one where samples are treated with the vapors, one where the vapors are created, and one including saturated salt solution (NaNO 2 : RH: 63 ± 1%; NaCl: RH: 75 ± 0%; KNO 3 : RH: 84 ± 1% at 25, 37, and 50°C) for altering RH of the interior atmosphere. Fumigation was performed for 2 hr at the interval time of 0, 1, and 2 hr (Hashemi & Jafarpour, 2020a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cold temperatures and a modified atmosphere can extend the storage time of strawberries, supplemental methods to maintain the fruit quality are being developed (Ghorbani et al., 2021). For example, edible coatings have recently been shown to improve product quality and increase shelf life periods of various fruits such as papaya and strawberries (Hashemi & Jafarpour, 2020; Tapia et al., 2008; Tarafdar et al., 2021). Coatings can provide moisture and gas permeability barriers and thus help with microbial growth control and protection of color and texture (Bourtoom, 2008; Hosseini et al., 2017; Mousavian et al., 2021).…”
Section: Introductionmentioning
confidence: 99%